2019
DOI: 10.1186/s13063-019-3689-5
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide and the management of overweight and obesity in people with schizophrenia, schizoaffective disorder and first-episode psychosis: protocol for a pilot trial

Abstract: BackgroundPeople with severe mental illness (SMI) are two to three times more likely to be overweight and obese than the general population and this is associated with significant morbidity and premature mortality. Although lifestyle interventions can support people with SMI to lose weight, some are unable to make the necessary lifestyle changes or, despite making the changes, continue to gain weight.ObjectiveTo assess the feasibility and acceptability of delivering a full-scale trial evaluating whether liragl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…These studies, however, used the doses used to treat diabetes. We therefore undertook a pilot feasibility to compare the use of liraglutide (maximum dose 3.0 mg daily) with placebo in obese or overweight people with schizophrenia, schizoaffective disorder or first episode psychosis [8,9]. This study demonstrated that although recruitment was challenging, once participants were enrolled, retention and adherence to the trial medication was similar to previous studies of liraglutide 3 mg daily in the general population.…”
Section: Introductionmentioning
confidence: 76%
“…These studies, however, used the doses used to treat diabetes. We therefore undertook a pilot feasibility to compare the use of liraglutide (maximum dose 3.0 mg daily) with placebo in obese or overweight people with schizophrenia, schizoaffective disorder or first episode psychosis [8,9]. This study demonstrated that although recruitment was challenging, once participants were enrolled, retention and adherence to the trial medication was similar to previous studies of liraglutide 3 mg daily in the general population.…”
Section: Introductionmentioning
confidence: 76%
“…The study protocol for this trial has been published previously 17 . In brief, we conducted a double‐blind, randomized, controlled pilot trial from 24 July 2018 (first patient, first visit) to 5 May 2020 (last patient, last visit) in mental health centres and primary care in Southern Health NHS Foundation Trust, UK (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…pancreatitis or an estimated glomerular filtration rate of less than 30 mL/min/1.73m 2 ), use of other pharmacological products for weight management, substance abuse or suboptimally managed diabetes defined by an HbA1c greater than 8% (>64 mmol/mol). A complete list of inclusion and exclusion criteria is available in Appendix S1 17 …”
Section: Methodsmentioning
confidence: 99%
“…Liraglutide has 97% homology to the human GLP-1 and was approved by the FDA in 2010. Like other GLP-1R agonists, it stimulates insulin secretion and inhibits glucagon release by the pancreas, delays gastric emptying, and reduces appetite (LIM et al, 2009;LÓPEZ-FERRERAS et al, 2018;MOJSOV, 2000;WHICHER et al, 2019). Due to its weight loss properties, liraglutide was repurposed by the Food and Drug Administration (FDA) in 2014 as a treatment for obesity.…”
Section: Glp-1r Agonists Are a New Drug Class Developed For Glycemic mentioning
confidence: 99%